PENGARUH SUMBER DAYA MANUSIA PENYIDIK TERHADAP KEBERHASILAN PENYIDIKAN (Studi Pada Satreskrim Polres Dharmasraya) - Ardhy Zul Hasbih Nasution (LPPM Universitas Ekasakti Padang, 2020)
The human resource capacity of the Satreskrim Polres Dharmasraya is still lacking due to the large number of criminal cases handled. The Influence of Human Resources of Investigators on the Success of Investigations at the Satreskrim at the Dharmasraya Police is the success of an investigation which is determined by whether or not an investigation is conducted. This influence can be measured by several criteria, namely the educational and vocational background (dikjur) of the investigators, at the Satreskrim of the Dharmasraya Police, investigators and assistant investigators who have participated in Dikjur in the field of criminal investigation or supporting the field of criminal investigation are 11 people during 2018. The number of investigators and assistant investigators is 34 people at the Satreskrim Polres Dharmasraya, so only 38 percent have a background in the field of Education and Culture in the field of criminal investigation or supporting in the field of criminal investigation. Experience conducting investigations. The efforts made and the obstacles faced by the Satreskrim of the Dharmasraya Police to fulfill the human resources of investigators was to increase the capacity of the Police Investigators so that they were able to understand and master laws / legal regulations. This can be pursued through improving education for members of the Satreskrim Polres Dharmasraya both formal and material education.